A pilot study on glycemia and insulin resistance in patients with severe periodontitis - Annie Kitty George; Vivek Narayan; Nisha Kurian; Annu Elizabeth Joseph; Sukumaran Anil (Wolters Kluwer Medknow Publications, 2021)
Context: The potential impact of severe periodontitis on glycemia in systemically healthy individuals is not clearly established. It was hypothesized that among individuals who were previously undiagnosed for diabetes mellitus, patients with severe periodontitis have impaired glycemia and insulin resistance. Aims: The aim of our study was to assess and compare glycemia in severe periodontitis patients and in individuals with clinically healthy periodontium. Materials and Methods: A cross-sectional analytical design was employed. From among individuals who were undiagnosed for diabetes mellitus, 37 patients with severe periodontitis and 37 individuals with healthy periodontium in the age group of 25-55 years were recruited for the study. The fasting blood sugar (FBS), glycosylated hemoglobin (HbA1c), and insulin resistance by the Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) were assessed and compared between the two groups. Results: The mean FBS, HOMA-IR, and HbA1c were significantly higher for patients with severe periodontitis than those individuals with healthy periodontium. After adjustments for age, gender, and body mass index, patients with severe periodontitis had a statistically significant association with impaired glucose metabolism (HbA1c ≥5.7) (adjusted odds ratio [OR] of 9.56; 95% confidence interval [CI]: 1.819-46.08; P < 0.01). Furthermore, patients with severe periodontitis had significantly greater odds to develop impaired fasting glucose (adjusted OR of 7.489, 95% CI: 1.408-39.839; P < 0.01). Conclusions: The mean FBS, HbA1c, and HOMA-IR were significantly higher in severe periodontitis patients than in the control group. A higher proportion of patients presented with prediabetes, incident diabetes, and insulin resistance in the severe periodontitis group.